2013
DOI: 10.1016/j.intimp.2013.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune semaphorin 4A as a drug and drug target for asthma

Abstract: Neuroimmune semaphorin 4A (Sema4A) has been shown to play an important costimulatory role in T cell activation and regulation of Th1-mediated diseases such as multiple sclerosis (MS), experimental autoimmune encephalomyelitis (EAE), and experimental autoimmune myocarditis (EAM). Sema4A has three functional receptors, Tim-2 expressed on CD4+ T cells, Th2 cells in particular, and Plexin B1 and D1 predominantly expressed on epithelial and endothelial cells, correspondingly. We recently showed that Sema4A has a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…Moreover, because Tim2-deficient mice demonstrated an enhanced lung Th2 inflammatory response to allergen challenge, it was concluded that Tim-2 is a negative regulator of Th2 responses (22). Additionally, the downregulatory effects of exogenous Sema4A in vivo in experimental models of asthma have been demonstrated (21,61), and the results of the in vivo use of Tim-2 blocking Ab had proven that there is another Sema4A receptor contributing to the allergic inflammatory disease pathogenesis (21). As there is no human homolog for Tim-2 (58), currently only two Sema4A receptors were found to be expressed on human CD4 + T cells, namely ILT-4 and Plexin B1, with potential positive or negative regulatory effects on CD4 + T cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, because Tim2-deficient mice demonstrated an enhanced lung Th2 inflammatory response to allergen challenge, it was concluded that Tim-2 is a negative regulator of Th2 responses (22). Additionally, the downregulatory effects of exogenous Sema4A in vivo in experimental models of asthma have been demonstrated (21,61), and the results of the in vivo use of Tim-2 blocking Ab had proven that there is another Sema4A receptor contributing to the allergic inflammatory disease pathogenesis (21). As there is no human homolog for Tim-2 (58), currently only two Sema4A receptors were found to be expressed on human CD4 + T cells, namely ILT-4 and Plexin B1, with potential positive or negative regulatory effects on CD4 + T cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The exacerbated inflammatory lung response in Sema4A 2/2 mice was accompanied by the significantly lower numbers of Treg cells in spleens and lungs, whereas this was the opposite for Sema4D 2/2 mice (19,20). Treatment of Sema4A 2/2 mice with recombinant Sema4A (rSema4A) resulted in not only significantly reduced allergic airway responses but also increased numbers of lung Treg cells (21). All these observations suggested the existence of a positive feedback loop between Sema4A and Treg cells that controls the allergic inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One emerging family of immune‐related molecules that have immune‐mediated disease properties is the semaphorin family (Vadasz & Toubi, ). Implicated in diseases such as rheumatoid arthritis and asthma, the semaphorin family has been shown to be a key component of immune disease progression (Chapoval, Vadasz, Chapoval, & Toubi, ; Koda et al, ; Mogie et al, ; Wang et al, ). Importantly, previous studies have shown that Sema4A binds to a member of the T‐cell immunoglobulin and mucin domain (Tim) family, Tim‐2 (Kumanogoh et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the opposite effects of Sema4A in autoimmune and allergic inflammatory diseases suggest that Sema4A promotes Th1 cell and suppresses Th2 cell responses. However, recombinant human Sema4A (rhSema4A) effectively inhibited already established allergic lung inflammation [ 9 ], and bone marrow chimeric mice demonstrated an equal importance of Sema4A expression on lung resident cells and bone marrow-derived inflammatory cells for optimal disease manifestation [ 8 ]. Thus, the function of Sema4A in autoimmune and allergic diseases is complex and affects many immune and non-immune cells.…”
mentioning
confidence: 99%